Clinical Benefit of Pembrolizumab in Lynch Syndrome‐Associated Advanced Ovarian Cancer With Germline MSH6 Variant: A Case Report - Tomomi Yokozawa; Sayako Nakagawa; Yukio Suzuki; Aya Tokinaga‐Uchiyama; Katsuyuki Konnai; Hiroto Narimatsu; Yukihiko Hiroshima; Haruya Saji (Clinical Case Reports, 2026)
ABSTRACT This case highlights the importance of genetic evaluation during treatment in young patients with advanced ovarian cancer. Lynch syndrome caused by a germline MSH6 pathogenic variant was diagnosed during first‐line maintenance therapy, and pembrolizumab achieved a durable response in recurrent disease.